Analysis of Thermal Effectiveness and Mass Flow Rate of Steam from Saturated to Superheater in Palm Oil Mill: Analisis Efektivitas Thermal dan Laju Aliran Massa Steam dari Saturated Menuju Superheater di Pabrik Kelapa Sawit - Andhi Fuad Bawazir; Zulham Effendi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
In the Palm Oil Mill (PKS) production system, the boiler is the main component that functions to produce steam for processing needs and turbine driving. The performance of the superheater plays an important role in improving steam quality by converting saturated steam into superheated steam, thereby supporting boiler operational efficiency. This study aims to analyze the thermal effectiveness of the superheater and determine the steam mass flow rate in the Takuma N-750 type boiler in the Palm Oil Mill. The research method used is descriptive quantitative with the collection of boiler operational data for five days of observation. The data analyzed include the superheater outlet steam temperature, operating pressure, steam density, and pipe cross-sectional area. The enthalpy value is determined through steam table interpolation using ChemicalLogic SteamTab Companion software. The results show that the superheater outlet steam temperature is in the range of 297.2–305.4°C with a stable operating pressure of 21 bar. The steam mass flow rate ranged from 23.28–26.71 tons/hour or 6.40–7.42 kg/second, with an average value close to the boiler design capacity of 27 tons/hour. The actual enthalpy value of the superheater outlet steam was in the range of 3014.75–3033.91 kJ/kg, while the design enthalpy was 3135.54 kJ/kg. The calculation results showed that the thermal effectiveness of the superheater was in the range of 96.1–96.7%, indicating that the heat transfer process was effective and relatively stable during the observation period. The stability of temperature, operating pressure, and mass flow rate indicated that the boiler operated at steady-state conditions with good system performance and was able to support the processing needs in the palm oil mill.